Male-female intermingling from the perspective of sunnah : a case study of KUIS students - Siti Salma binti Mohamad Shokri (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
The focus of this study is to examine and investigate the understanding as well as the awareness of Kolej Universiti Islam Antarabangsa Selangor (KUIS)‟s students with regard to intermingling between male and female. Of late, neglecting the issue of free intermingling between the opposite sexes has given rise to bad consequences in the society, and the first step we must take is to tackle the root cause of the problem by following the Prophetic tradition significantly. Thus, a survey research will be conducted involving KUIS students in order to gather information to gauge the seriousness of the intermingling between sexes by distributing questionnaires as a method of study. The data were collected and analyzed using a descriptive statistic method in Statistical Package for the Social Sciences (SPSS). The researcher will also employ the library research by reviewing previous literature written as well as the books related to this topic. The conclusion reached for this research is that most of the KUIS students do understand and have knowledge with regard the aÍÉdÊth related to intermingling between sexes. Without any doubt, we must act upon the knowledge by following the path and guidance from Qur´Én and Sunnah seriously and from there, the social problem which occurred nowadays may be reduced because Islam nevertheless seeks prevention over remedy.